2023
DOI: 10.3389/fimmu.2022.1084139
|View full text |Cite
|
Sign up to set email alerts
|

Immune escaping of the novel genotypes of human respiratory syncytial virus based on gene sequence variation

Abstract: PurposeImmune escaping from host herd immunity has been related to changes in viral genomic sequences. The study aimed to understand the diverse immune responses to different subtypes or genotypes of human respiratory syncytial virus (RSV) in pediatric patients.MethodsThe genomic sequences of different subtypes or RSV genotypes, isolated from Beijing patients, were sequenced and systematically analyzed. Specifically, the antiviral effects of Palivizumab and the cross-reactivity of human sera from RSV-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Significant differences have been observed between RSV prototype strains and contemporary clinical isolates, including variations in viral replication kinetics, thermal stability, fusion capacity and the nAbs they induce. Therefore, utilizing contemporary isolates ensures a more representative assessment of vaccine efficacy against current circulating viruses [ 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. Moreover, it could be considered highly desirable to include multiple recent isolates of RSV instead of using just one.…”
Section: Current Challengesmentioning
confidence: 99%
“…Significant differences have been observed between RSV prototype strains and contemporary clinical isolates, including variations in viral replication kinetics, thermal stability, fusion capacity and the nAbs they induce. Therefore, utilizing contemporary isolates ensures a more representative assessment of vaccine efficacy against current circulating viruses [ 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 ]. Moreover, it could be considered highly desirable to include multiple recent isolates of RSV instead of using just one.…”
Section: Current Challengesmentioning
confidence: 99%
“…The diversity observed in this study may have an impact on the contagiousness and severity of HBoV1 infections. This could be linked to mutations in the capsid proteins that are involved in attachment of the virus to its host cell, as has been observed for other viruses such as SARS‐CoV‐2 for which mutation in the spike glycoprotein was associated with a high contagiousness 39 or the respiratory syncytial virus for which capacities of immune response were reported to vary according to the viral genotype 40 . Further studies are needed to gain a better knowledge about these points and the impact of given mutations.…”
Section: Discussionmentioning
confidence: 88%
“…This could be linked to mutations in the capsid proteins that are involved in attachment of the virus to its host cell, as has been observed for other viruses such as SARS-CoV-2 for which mutation in the spike glycoprotein was associated with a high contagiousness 39 or the respiratory syncytial virus for which capacities of immune response were reported to vary according to the viral genotype. 40 Further studies are needed to gain a better knowledge about these points and the impact of given mutations. Intriguingly, stop codons were observed in three genomes from the present study and also in genomes from GenBank at different genome positions.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies targeting the F protein are critical for developing RSV vaccines aiming to prevent infection ( Ruckwardt et al, 2019 ). Recent neutralization assays conducted in China revealed that pediatric patients infected with different subtypes/genotypes of HRSV exhibited varying antibody titers against different subtypes/genotypes of HRSV ( Zhou et al, 2023 ). Our study identified amino acids changes at antigenic sites Ø, I, II and VIII within the F protein.…”
Section: Discussionmentioning
confidence: 99%